2018
DOI: 10.1016/j.conbuildmat.2018.04.100
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and statistical study on the irregularity of carbonation depth of cement mortar under supercritical condition

Abstract: The heterogeneity of a cement-based material results in a random spatial distribution of carbonation depth. Currently, there is a lack of both experimental and numerical investigations aiming at a statistical understanding of this important phenomenon. This paper presents both experimental and numerical supercritical carbonation test results of cement mortar blocks. The carbonation depths are measured along the carbonation boundary by the proposed rapid image processing technique, which are then statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Thus, probabilistic analyses are useful to quantify these unavoidable uncertainties. Hao proposed that the probability density functions of carbonation depth agree well with the lognormal distribution [26]. Meanwhile, Hao found that the average and variance augment with the increase of time.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, probabilistic analyses are useful to quantify these unavoidable uncertainties. Hao proposed that the probability density functions of carbonation depth agree well with the lognormal distribution [26]. Meanwhile, Hao found that the average and variance augment with the increase of time.…”
Section: Introductionmentioning
confidence: 82%
“…Due to variations associated with climatic factors (e.g., temperature and humidity), concrete materials properties and geometric configuration [24,25], it is physically impossible to evaluate carbonation depths precisely. Several studies have demonstrated that carbonation depth is characterized by significant dispersion [26,27]. Thus, probabilistic analyses are useful to quantify these unavoidable uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Since the presence of variations associated with climatic factors (e.g., temperature and humidity), concrete materials, and geometric configurations [18,19], the compressive strength of concrete should be regarded as a variable in order to account for these uncertainties in deterioration. In practical engineering problems, these unavoidable uncertainties are often qualified by probabilistic models [20][21][22], among which reliability analyses are widely applied in structural safety assessments [23][24][25]. In the existing time-varying reliability models, the probabilities of corrosion initiation and corrosion damage are calculated based on the change in climatic variables [26].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, the distribution of carbonation depth is irregular with distinctive minimum and maximum along the boundary of a carbonation zones under both natural [27] and supercritical [28][29][30] conditions. However, the irregularities cannot been predicted by most carbonation models that assumed all cement-based materials are homogenous [31] , resulting in uniform carbonation depth [32] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the irregularities cannot been predicted by most carbonation models that assumed all cement-based materials are homogenous [31] , resulting in uniform carbonation depth [32] . In fact, the topography of carbonation depth is affected by the presence of coarse aggregate [12,33,34] , cracks [35][36][37] , porosity of cement [29,30,38] , porosity of the Interfacial Transition Zone (ITZ) [39,40] and compositions of concrete [41,42] . To statistically study the distribution of irregular carbonation depth, Alahmad, et al [43] showed that penetration and diffusion of CO2 were significantly affected by cracks in cement mortar.…”
Section: Introductionmentioning
confidence: 99%